Immunolocalization of 3ß-hydroxysteroid dehydrogenase (3ß-HSD) in the testis of lesser mouse deer (Tragulus javanicus) - Sriyanto,; Saad, Mohd Zamri; Agungpriyono, Srihadi; Abu Bakar @ Zakaria, Md Zuki; Haron, Abd Wahid (Universiti Putra Malaysia Press, 2011)
The present study describes the location of 3ß-hydroxysteroid dehydrogenase in the testis of lesser mouse deer (Tragulus javanicus) using immunoperoxidase technique. Testicular samples were obtained from 4 adult male lesser mouse deer; two samples were collected during the dry and the other 2 samples during the wet season. All the samples were subjected to immunoperoxidase staining technique to determine the localization of 3b-hydroxysteroid dehydrogenase (3ß-HSD), an enzyme that plays a central role in biosynthesis of steroid hormones, including androgen and oestrogen and an indicator for spermatogenesis activity. The positive reactions were observed in the Leydig, Sertoli, and spermatogonia cells of all animals. The number of positive Leydig cells was significantly (p<0.05) higher in the testes sampled during the dry season while the number of positive Sertoli cells was significantly (p<0.05) higher in the testes of animals that were sampled during the wet season. However, the total number of cells showing positive reactions remained insignificantly (p<0.05) different in all the animals.